Experimental study of organic Rankine cycle with three-fluid recuperator for cryogenic cold energy recovery. (1st March 2022) - Tian, Zhen; Gan, Wanlong; Qi, Zhixin; Tian, Molin; Gao, Wenzhong
Abstract: In this paper, experimentally studies of a 1 kW-scale organic Rankine cycle (ORC) with R290 as working medium were carried out for cryogenic cold energy recovery. Specifically, a three-fluid wounded tube heat exchanger was utilized as the condenser and the recuperator, which made the system operate under the basic ORC (bORC) and the recuperative ORC (rORC) working modes. The hot water and the liquid nitrogen were respectively used as the heat source and cold source. The system performances were evaluated at 20–50 °C of the heat source, −170∼-160 °C and 60–120 kg/h of the cold source. The optimal heat source temperatures were obtained for the different cold source conditions. Moreover, the superiority of the rORC was verified. The results demonstrated that the maximum net power outputs were 0.673 kW and 0.894 kW for the bORC and rORC, respectively. For the bORC and the rORC, the maximum energy efficiency was 5.23% and 6.49%, and the maximum exergy efficiency was 21.34% and 28.99%, respectively. The cold energy efficiency varies in the range of 1.73%–14.20% and 1.16%–19.72% for the bORC and rORC, respectively. The three-fluid recuperator occupied the largest exergy loss, which varied in the range of 66.59–84.12%. Highlights: An ORC with three-fluid recuperator was proposed for cryogenic cold energy recovery. The optimal heat source temperatures were obtained under different conditions. With the recuperator, the maximum energy efficiency increased from 5.23% to 6.49%. The cold energy efficiency could be increased by 101.7% via the recuperative process. The three-fluid recuperator occupied the largest exergy loss ratio.